2019
DOI: 10.1080/09540105.2019.1580677
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of astilbin partially via calcium channels through regulation on CaMKII

Abstract: This study aimed to evaluate the analgesic efficacy of astilbin and its underlying mechanisms. Astilbin suppressed the symptoms of acetic acid-induced writhing, lengthened the latency period on the hot plate, and reduced the licking and biting response of formalin-injected mice, suggesting its analgesic efficacy on the central nervous system. Astilbin suppressed neuronal nitric oxide synthase and enhanced serotonin and norepinephrine in serum and brains of mice after 30 s of thermal stimulation, but it failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…CaM is the critical effector of Ca 2+ . Furthermore, CaMKII, one of the main downstream targets of Ca 2+ and CaM, is activated by Ca 2+ /CaM (Bi et al, 2019;Chin & Means, 2000;Ohmori & Hamilton, 1992). To further elucidate the role of CaM and CaMKII in the inhibition of macrophage activation by three alkaloids, the expression of CaM, phosphorylated-CaMKII and total CaMKII was detected by western blot assay.…”
Section: Effects Of Neferine Liensinine and Isoliensinine On The Expmentioning
confidence: 99%
“…CaM is the critical effector of Ca 2+ . Furthermore, CaMKII, one of the main downstream targets of Ca 2+ and CaM, is activated by Ca 2+ /CaM (Bi et al, 2019;Chin & Means, 2000;Ohmori & Hamilton, 1992). To further elucidate the role of CaM and CaMKII in the inhibition of macrophage activation by three alkaloids, the expression of CaM, phosphorylated-CaMKII and total CaMKII was detected by western blot assay.…”
Section: Effects Of Neferine Liensinine and Isoliensinine On The Expmentioning
confidence: 99%
“…Astilbin (Figure 1), a flavonoid glycoside, is one compound recently isolated from L. strychnifolium (Sampaopan et al, 2021), specifically found in extracts (Bi et al, 2019;Lu et al, 2015). The astilbin is separated from the extracts by column chromatography (Merck silica gel 60, 70-230 mesh) eluted with ethyl acetate and methanol (95: 5, %v/v), and reversed-phase column chromatography (Merck LiChroprep RP-18, 40-63 µm) eluted with methanol and water (50: 50, % v/v).…”
Section: Introductionmentioning
confidence: 99%